Geometric mean labeling on Degree splitting graphs. (3rd March 2016) - Somasundaram, S.; Sandhya, S. S.; Viji, S. P.
Abstract: A Graph G = ( V, E ) with p vertices and q edges is said to be a Geometric mean graph if it is possible to label the vertices x ϵ V with distinct labels f ( x ) from 1, 2 … … … … q + 1 in such a way that when each edge e = uv is labeled with f ( e = uv ) = ⌈ f ( u ) f ( v )⌉ or ⌊ f ( u ) f ( v )⌋, then the resulting edge labels are distinct. In this case, f is called Geometric mean labeling of G . In this paper we study the Geometric mean labeling on Degree Splitting graphs.